The blackout: The apocalypse of the letters in a digital word. The short film as a didactic proposal for reading and writing in the ELE classroom - Navarro Ayensa, Mikel (2019)
We present a filmic and linguistic analysis of the short film The blackout as a methodological proposal to work and develop reading and writing skills in the language classroom, and specifically, in the ELE classroom. The objective is to provide slogans for the intertextuality of the images and their expression in the written expression. In this way, it is possible to bring the possibilities offered by “the short” to the teaching and learning of language and culture to students at secondary and university education levels. The methodology used is based on the description and comment of scenes and activities to implement in the classroom in a pragmatic way.